A Formal Model for Performance and Energy Evaluation of Embedded Systems. (29th September 2010) - Nogueira Nogueira, Bruno Bruno; Maciel Maciel, Paulo Paulo; Tavares Tavares, Eduardo Eduardo; Andrade Andrade, Ermeson Ermeson; Massa Massa, Ricardo Ricardo; Callou Callou, Gustavo Gustavo; Ferraz Ferraz, Rodolfo Rodolfo
Abstract : Embedded systems designers need to verify their design choices to find the proper platform and software that satisfy a given set of requirements. In this context, it is essential to adopt formal-based techniques to evaluate the impact of design choices on system requirements. To be useful, such techniques must produce accurate results with minimal computation time. This paper proposes an approach based on Coloured Petri Nets for evaluating embedded systems performance and energy consumption. In particular, this work presents a method for specifying and evaluating the workload and the platform components, such as processors and shared or private memories. The method is applied to model single processor and multiprocessor platforms. Experimental results demonstrate an average accuracy of 96% in comparison with the respective measures assessed from the real hardware platform.